Implementation of E-Learning System in Distance Education Management during the Covid-19 Pandemic - Bayu Prabowo Sutjiatmo; Aji Kresno Murti (Departement of Mathematics Education, 2021)
The Covid-19 situation has forced the education system to adjust to remote or online learning. Social restriction and lockdown policies caused schools and universities to be closed to avoid the spread of the virus. This study aims to analyse the implementation of e-learning systems in distance education management during the Covid-19 pandemic, with a little focus on the factors that affect the success of implementation and student performance in distance learning. The focus here is on qualitative analysis. Listening to and recording pertinent information was an integral part of data collection, which was followed by data reduction, data display, and inference. This study found that the implementation of an e-learning system in distance education management during the COVID-19 pandemic is an important step that needs to be taken to ensure the continuity of education and the health of students and teaching staff. The e-learning system provides flexibility in learning and allows students to stay connected with teaching staff despite limited face-to-face interaction.